A tale of two bacteria – Bacteroides fragilis, Escherichia coli, and colorectal cancer - Lichtenstern, Charles Robert; Lamichhane-Khadka, Reena (Frontiers in Bacteriology, 2023)
Colorectal cancer (CRC) is a leading cause of cancer-related deaths globally. Incidence rates among individuals under 50 years are rising, which has led to the lowering of the recommended screening age from 50 to 45 years for those at an average risk. While numerous risk factors are associated with the development of CRC, most cases contain microbial signatures representative of dysbiosis, indicating a role for the gut microbiome in disease pathogenesis. To date, most research has investigated individual members of the gut microbiota independently; however, it is widely established that microbes interact with each other in the gut. More recently, two specific species of the microbiota have revealed a pro-carcinogenic synergism in vivo. Strains of both Bacteroides fragilis and Escherichia coli have been linked to CRC in clinical studies and been shown to induce carcinogenesis in mouse models through B. fragilis toxin and colibactin,respectively. The link between these two bacteria is found within their spatial association: biofilms,